Dysfunctions of the System of Rewarding in the Organization - Oleksiak, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
A purpose of the article is show at the overview of basic dysfunctions of systems of rewarding in the organization. In particular these dysfunctions concern the motivating function of rewarding in the reference to different of his elements: systems of awarding a bonus, assessing the work, tables of pays or extra benefits. These characteristics were supplemented with research findings, of concerning systems of rewarding in enterprises.